Rescuing the ectomycorrhizal biodiversity associated with South American Nothofagaceae forest, from the 19th century naturalists up to molecular biogeography - Barroetaveña, Carolina; Salgado Salomón, María Eugenia; Bassani, Vilma (Forestry: An International Journal of Forest Research)
The southernmost portion of the Andes in South America hosts Nothofagaceae forests that form ectomycorrhizal (EcM) associations. We compiled all the published reports of EcM taxa from these woodlands, based on fruit-body collections and molecularly identified root tips. This resulted in 87 peer-reviewed research papers dealing with EcM associations from Nothofagaceae forests published over the past 62 years. Based on these papers the EcM richness and its association with Nothofagaceae species was analyzed. Represented by 45 genera (34 Basidiomycetes and 11 Ascomycetes), 479 EcM taxa have been recorded, plus an additional 46 EcM taxa which are potentially EcM. Cortinarius was the most frequent and diverse genus, with 64.9% of total species. Nothofagus dombeyi had the highest number of unique EcM species, followed by N. pumilio, N. antarctica and Lophozonia obliqua. The EcM community associated with Nothofagus species, except N. nitida, showed higher similarities among themselves, than with Lophozonia and Fuscospora species. Beta diversity indexes showed EcM Nothofagus species have 29-42% niche overlap, while Nothofagus-Lophozonia only had 1-16%. The assessment of the accuracy of the EcM diversity, host specificity and community structure deserve further studies combining phylogenetic analysis based on broad ecological surveys. On the basis of pre-selected criteria Austropaxillus statuum, Cortinarius fragilis, Cortinarius xiphidipus and Hallingea purpurea are proposed as candidates for nursery spore inoculations, and should be subject to scientific evaluation to determine costs and benefits. Fil: Barroetaveña, Carolina. Universidad Nacional de la Patagonia "san Juan Bosco". Facultad de Ingeniería - Sede Esquel. Cátedra de Patología Forestal; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Centro de Investigación y Extensión Forestal Andino Patagónico; Argentina Fil: Salgado Salomón, María Eugenia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Centro de ...